Using Technology for Learning: Generalizable Lessons from Educational Technology Integration in Kenya - Arshad-Ayaz, Adeela; Naseem, M. Ayaz; Inyega, Justus O. (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie)

(untitled) (The Canadian Network for Innovation in Education, 2022)
This paper presents some initial findings from a multi-year partnership project on the integration of technology into the Kenyan education system. Specifically, qualitative evidence is presented on how results and lessons learned from the partnership project can be generalized and used by other research teams and projects using other technology platforms. Grounded in the critical theory of educational technology and using methodological strategies on the intersections of critical discourse analysis and critical ethnography, this paper examines technology integration in Kenyan public schools using the Learning Toolkit+ developed at the Centre for the Study of Learning and Performance at Concordia University in Montreal, Canada.